The Influence of Brand Image, Promotional Attractiveness, and Halal Awareness on Purchasing Decisions through Purchase Interest in Bread Product. - rizal ariadi; Rosana Eri Puspita (Dinamis : Journal of Islamic Management and Bussiness, 2024)
Along with the growth of technology that affects science, culture, and technology, consumers also receive various information that affects consumer lifestyles, one of which is the development of food consumption. Currently, most people prefer fast food and convenience food, so the average food consumption in Indonesia is relatively high. This study was conducted to analyze the influence of brand image, promotional attractiveness and halal awareness on purchasing decisions with purchase interest as an intervening variable and using respondents of Aoka Bread consumers in Semarang Regency. This study used quantitative research using multiple linear regression analysis. The sampling technique uses purposive sampling with a total of 100 respondents. The results of the T-test showed that brand image does not have a positive and significant effect on purchasing decisions, promotional attractiveness has a positive and significant effect on purchasing decisions, halal awareness does not have a positive or significant effect on purchasing decisions, and buying interest has a positive and significant effect on purchasing decisions. The results of the F test showed that simultaneously, brand image, promotional attractiveness, and halal awareness affect purchasing decisions, and simultaneously, brand image, promotional attractiveness, and halal awareness affect consumer buying interest. For future research, it is recommended to choose a different case study and includes additional variables. This will strengthen understanding and provide deeper insight into how consumers know the product and so that interest in buying again.